Optimization and Performance Evaluation of Foam Discharge Agent for Deep Aquatic Condensate Gas Well - Ge, Lei; Cui, Hailin; Li, Yingchao; Sui, Xiuan (Frontiers in Physics, 2022)
The block deep condensate gas reservoir in the basin in the southeast of the South China Sea is a bottom water reservoir and is producing in the late effusion, which faces problems such as scaling, condensate oil–water two-phase flow, and low temperature at the subsea wellhead. The mud line for this kind of gas-well has characteristics including high condensate content in low temperature, high downhole temperature, and injection with a foam discharge agent and scale inhibitor. In this article, the influence of low temperature and scale inhibitor is considered for the first time, and a dynamic liquid-carrying experiment for the optimization and performance evaluation of foam discharge agents was carried out according to these characteristics. The experimental results show that the optimized foam discharge agent, ZHY-01, has good resistance to high temperature and condensate oil, and the optimal concentration of the foam discharge agent is recommended to be 0.25%. Under this concentration, the liquid-carrying capacity of the foam discharge agent decreases slightly by 10.17% at low temperature. The scale inhibitor MA/AA reduced the liquid-carrying capacity by 11.86%, and the scale inhibitor PESA reduced the liquid-carrying capacity by 10.17%. The research results in this article have certain reference significance for the chemical screening and evaluation of the foam drainage gas production process in deep-water condensate gas wells.